Vegetable of Knowledge - Othman, Nur Adilah; Mhd. Sarif, Suhaimi (2020)
This creative work explains the value of knowledge resembles the value of vegetables. A group of students visited vegetable garden and inspired to write poem about a theme on the vegetables.